PENGARUH PENYULUHAN DENGAN METODE DEMONSTRASI TENTANG CUCI TANGAN PAKAI SABUN (CTPS) TERHADAP KETERAMPILAN CUCI TANGAN PADA ANAK-ANAK DI KAMPUNG NOLOKLA SENTANI TIMUR - Mofu, Renold Markus (NHM PRESS, 2022)
Papua Province recorded the lowest access rate of 35% in correct hand washing behavior with soap. The design of this study was a quasi-experimental with one group pre-test and post-test design. The population is all children aged 6-12 years in the village of Nolokla Sentani Timur totaling 45 people. Sampling technique with total sampling. Statistical test using Wilcoxon test. Results: The average value of the handwashing with soap (CTPS) skill 6 steps before counseling using the demonstration method was 55.47 and the average value after counseling using the demonstration method was 83.89. There is an effect of counseling using the demonstration method on hand washing with soap (CTPS) on hand washing skills in children in Nolokla Village, East Sentani District with p value 0.000 (<0.05). Suggestions to improve counseling with demonstration methods on other health education.